A Systematic Review on the Renewable Energy Development, Policies and Challenges in Nigeria with an International Perspective and Public Opinions - Ugwu, Justin; Salami, Kehinde Oseni; Oluka, Leonard Onyedikachi; Odo, Kenneth Chinonso (International Journal of Renewable Energy Development, 2022)
Due to the threat posed by fossil fuels to human existence; many countries around the world have turned attention to renewable sources for power generation to reduce the emission of greenhouse gases and stop ozone layer depletion. This has increased the exploitation of various renewable energy sources which include: hydro, biomass, solar, geothermal and wind in many developed countries. However, most African countries seem not to have awakened to this new reality. This work presents a comprehensive review of available renewable energy capacity in Nigeria, the level of utilization of renewables in Nigeria in comparison to other countries, comparison of renewable energy scenarios among African countries, factors hindering the development of renewables in Nigeria, the country’s renewable energy policy and ways of improving its status in the country. A lot of peer-reviewed journal articles, and grey literatures were gathered from which the most suitable ones were selected for reviews. In addition, opinions of people across the country and beyond, regarding renewable energy status in Nigeria were sought through a questionnaire. It is found that Nigeria is greatly endowed with different renewable energy sources but the level of utilization has been very low due to a myriad of factors such as non-implementation of renewable energy policies, financial issues, unfavorable government policies and lack of adequate research. It is expected that the findings in this work will awaken policies makers in Nigeria to reshape her renewable energy policies and speed up its implementation as well as guide individuals wishing to invest in the nation’s vast renewable resources.